Diabetes management in patients undergoing total pancreatectomy: A single center cohort study - Zhao, Tianyi; Fu, Yong; Zhang, Taiping; Guo, Junchao; Liao, Quan; Song, Shuoning; Duo, Yanbei; Gao, Yuting; Yuan, Tao; Zhao, Weigang (Frontiers in Endocrinology, 2023)
Background: Total pancreatectomy (TP) has been increasingly performed in recent years. However, studies on diabetes management after TP during different postoperative periods are still limited. Objectives: This study aimed to evaluate the glycemic control and insulin therapy of patients undergoing TP during the perioperative and long-term follow-up period. Methods: Ninety-three patients undergoing TP for diffuse pancreatic tumors from a single center in China were included. Based on preoperative glycemic status, patients were divided into three groups: nondiabetic group (NDG, n = 41), short-duration diabetic group (SDG, preoperative diabetes duration ≤12 months, n = 22), and long-duration diabetic group (LDG, preoperative diabetes duration >12 months, n = 30). Perioperative and long-term follow-up data, including the survival rate, glycemic control, and insulin regimens, were evaluated. Comparative analysis with complete insulin-deficient type 1 diabetes mellitus (T1DM) was conducted. Results: During hospitalization after TP, glucose values within the target (4.4-10.0 mmol/L) accounted for 43.3% of the total data, and 45.2% of the patients experienced hypoglycemic events. Patients received continuous intravenous insulin infusion during parenteral nutrition at a daily insulin dose of 1.20 ± 0.47 units/kg/day. In the long-term follow-up period, glycosylated hemoglobin A1c levels of 7.43 ± 0.76% in patients following TP, as well as time in range and coefficient of variation assessed by continuous glucose monitoring, were similar to those in patients with T1DM. However, patients after TP had lower daily insulin dose (0.49 ± 0.19 vs 0.65 ± 0.19 units/kg/day, P < 0.001) and basal insulin percentage (39.4 ± 16.5 vs 43.9 ± 9.9 %, P = 0.035) than patients with T1DM, so did those using insulin pump therapy. Whether in the perioperative or long-term follow-up period, daily insulin dose was significantly higher in LDG patients than in NDG and SDG patients. Conclusions: Insulin dose in patients undergoing TP varied according to different postoperative periods. During long-term follow-up, glycemic control and variability following TP were comparable to complete insulin-deficient T1DM but with fewer insulin needs. Preoperative glycemic status should be evaluated as it could guide insulin therapy after TP.